Toronto Cupcakes E-Commerce Powered by React JS Frameworks for User-Centric Design (Journal of Digital System Development, 2024)
In 2013, Facebook introduced React.js to the world, and it has since gained widespread popularity as a tool for front-end development. React.js is a JavaScript library that allows developers to build user interfaces using a component-based approach. This means developers can break down complex UIs into smaller, reusable components, making it easier to manage and update the codebase. In addition, React.js utilises a virtual Document Object Model (DOM), which allows for faster rendering and better performance compared to traditional methods. This paper emphasises the vital role of user-centric design in boosting customer satisfaction and business success in e-commerce. It examines current challenges and proposes a solution, showcasing how addressing usability issues can benefit small businesses like Toronto Cupcakes by prioritising essential features and creating a responsive, mobile-friendly website prototype.